Determination Factors Associated with Psychological Outcomes of Healthcare Workers during the COVID-19 Pandemic and its Effects on Quality of Life - Hanin Abdulhameed Shalaby; Nora Baroom; Rawan Anwar Obaid; Enaam Raboe (Issues and Development in Health Research Vol. 6, 2021)
Purpose: Healthcare workers (HCWs) are exposed to stressful working conditions during the Coronavirus disease 2019 (COVID-19) pandemic, which is affecting their quality of life (QoL). The purpose of the present research is to assess in-depth the main factors associated with psychological outcomes among HCWs in Saudi Arabia during the COVID-19 pandemic and to gauge the effects of these outcomes on the HCWs’ QoL. Methodology: In this descriptive cross-sectional study, all HCWs working in tertiary hospitals in Saudi Arabia who have direct or indirect contact with COVID-19 cases were invited voluntarily to complete a validated web-based survey during the study period.Between the 1st of June and the 31st of July 2020, 1,182 HCWs from various regions across SA and specialties, including physicians, nurses, pharmacists, health educators, technicians, and others, participated in this study. The Patient Health Questionnaire depression scale and the Generalized Anxiety Disorder (GAD-7) anxiety scale were used to assess psychological risk factors. World Health Organization Quality of Life Questionnaire(WHOQOL) was used to assess QoL. Socio-demographic information was summarised using frequency and percentages. The study participants’ overall anxiety, depression, and WHOQOL scores were calculated using mean, standard deviation, and median values.The relationship between socio-demographic factors and anxiety and depression scales was investigated using independent samples t-tests, one-way ANOVA, and the chi-square test (for categorical depression/anxiety variables severe depression/severe anxiety against mild/moderate/moderately severe).While one-way ANOVA was used to examine those factors and WHOQOL domains. The front-line work predictors of depression and anxiety were identified using multivariate analysis. Findings: Poor QoL scores were found, particularly in the domains of physical and psychological health. Workers who reported higher levels of anxiety and depression had significantly higher QoL in general. Age, gender, living with children and/or older people, occupation, years of experience, and participation in front-line work were all observed as factors affecting psychological health and QoL. Unique Contribution to Theory, Practice and Policy: In terms of depression, anxiety, and QoL, certain traits of HCWs may operate as protective or risk factors. Targeted interventions could help medical professionals preserve their mental and physical health by reducing the harmful impacts of front-line work. More research is needed to learn more about how the COVID-19 epidemic and front-line work effect the mental and physical health of HCWs.